Effect of supplemental milk replacer and liquid starter diet for 4 and 11 days postweaning on intestinal parameters of weaned piglets and growth to slaughter - S.R. Vasa; G.E. Gardiner; E.A. Arnaud; K. O’Driscoll; G. Bee; P.G. Lawlor (Animal, 2024)
Reduced piglet feed intake immediately postweaning (pw) leads to disruption of small intestine structure and function and reduced growth. Our objective was to evaluate the effect of providing supplemental milk or liquid starter diet for either 4 or 11 days pw, on intestinal parameters of newly weaned piglets and growth to slaughter. At weaning (28 ± 0.6 days old), five hundred and eighty−seven piglets ((Large White × Landrace) × Duroc) were divided into 59 pen groups, each containing 9–10 same sex (entire male or female) piglets. The pen groups were blocked by sex and weaning weight and provided with ad-libitum access to one of five dietary treatments: (1) Dry pelleted starter diet (control; CON); (2) CON+liquid milk replacer for 4 days pw (M4); (3) CON+liquid milk replacer for 11 days pw (M11); (4) CON+liquid starter diet for 4 days pw (S4) and (5) CON+liquid starter diet for 11 days pw (S11). Pen groups were weighed at weaning, days 11, 20, 28, and 47 pw and at target sale weight. Feed disappearance (on a DM basis) was recorded on each weighing day. On day 7 pw, 10 piglets per treatment were euthanised to collect small intestine tissue samples for determination of villus height (VH), crypt depth and brush-border membrane enzyme activity. Data were analysed using SAS-version 9.4. Between days 0 and 11 pw, M11 increased average daily feed intake by 48% and average daily gain (ADG) by 57% compared to CON (P < 0.05), and increased ADG by 54% (P < 0.05) compared to S4. Piglets on M11 also had improved feed conversion efficiency compared with CON piglets between days 0 and 11 pw. Treatment did not affect growth performance after day 28 pw, or carcass parameters at slaughter. At day 7 pw, M11 piglets had 37% higher jejunal VH than CON piglets (P < 0.05) and S11 piglets had 28% higher ileal VH than S4 piglets (P < 0.05). M11 piglets had up to 150% higher ileal sucrase activity than M4, S4 and S11 piglets (P < 0.05) and 180% higher ileal maltase activity than S4 piglets (P < 0.05). In conclusion, M11 reduced the immediate negative effects of weaning, as it was associated with increased feed intake, growth, brush-border membrane enzyme activity and improved intestinal structure early pw. However, there were no carryover effects of any of the liquid supplements on growth or feed efficiency or carcass weight at slaughter.